Climatic conditions produce contrasting influences on demographic traits in a long‐distance Arctic migrant. (23rd January 2017) - Cleasby, Ian R.; Bodey, Thomas W.; Vigfusdottir, Freydis; McDonald, Jenni L.; McElwaine, Graham; Mackie, Kerry; Colhoun, Kendrew; Bearhop, Stuart
Summary: The manner in which patterns of variation and interactions among demographic rates contribute to population growth rate (λ) is key to understanding how animal populations will respond to changing climatic conditions. Migratory species are likely to be particularly sensitive to climatic conditions as they experience a range of different environments throughout their annual cycle. However, few studies have provided fully integrated demographic analyses of migratory populations in response to changing climatic conditions. Here, we employed integrated population models to demonstrate that the environmental conditions experienced during a short but critical period play a central role in the demography of a long‐distance migrant, the light‐bellied Brent goose ( Branta bernicla hrota ). Female survival was positively associated with June North Atlantic Oscillation (NAO) values, whereas male survival was not. In contrast, breeding productivity was negatively associated with June NAO, suggesting a trade‐off between female survival and reproductive success. Both adult female and adult male survival showed low temporal variation, whereas there was high temporal variation in recruitment and breeding productivity. In addition, while annual population growth was positively correlated with annual breeding productivity, a sensitivity analysis revealed that population growth was most sensitive to changes in adult survival. Our results demonstrate that the environmental conditions experienced during a relatively short‐time window at the start of the breeding season play a critical role in shaping the demography of a long‐distant Arctic migrant. Crucially, different demographic rates responded in opposing directions to climatic variation, emphasising the need for integrated analysis of multiple demographic traits when understanding population dynamics. Abstract : The article provides a truly integrated analysis of the effect of climate on the demography of a long‐distance migrant at the scale of the flyway population. We found that different demographic traits responded to the climate in opposing ways, highlighting the complexity of predicting population responses to climate change. Photo credit: F. Vigfusdottir.